Identification of common sitting postures of aircraft passengers through observation method - Romli, Fairuz Izzudin; Aminian, Negin Ozve; Hamzah, Norfara Aiza (International Journal of Recent Technology and Engineering, 2019)
Passenger comfort is an important feature that can increase the competitiveness of flight services of an airline against its market competitors. The aircraft seat design plays a big role in promoting comfort for aircraft passengers, especially in relation to the sitting postures that it can support. In order to conduct the ergonomics assessment on the seat design, the sitting postures of the aircraft passengers have to be established. This study aims to identify some of common sitting postures of the flying passengers inside the aircraft cabin by means of the observation method. 10 volunteers are recruited and they are individually recorded while sitting on a representative aircraft seat for about an hour. Based on the obtained recordings, common postures have been identified based on their frequency of occurrence among the volunteers. All in all, eight common sitting postures have been identified and they can be used in the posture analysis